Paralyzing paradox: Spinal cord infarction, a hidden emergency - Khurram Khaliq Bhinder; Khizer Ahmed Khan; Madiha Saeed Wahla; Amna Mehboob; Abeer Shahid; Alishbah Ziad (Radiology Case Reports)
Spinal cord infarction is a rare entity that is encountered less but has a high mortality and morbitiy rate. 43 years old female presented to emergency department with acute lower limb weakness. Urgent MRI was performed that showed long segment intramedullary signal abnormality involving anterior and middle half of cervical spinal cord, showing restricted diffusion and possible questionable faint enhancement. Another smaller similar abnormal signal intensity intramedullary focus at T1-T2 level. No heterogenous signal or abnormal enhancement was noted in adjacent visualized vertebral bodies. Considering restricted diffusion first differential possibility is of anterior spinal cord ischemia/infarct with no fever or trauma history. This is a rare case presentation of spinal infarct in Pakistan presenting acutely.